Paternally expressed imprinted genes associate with hybridization barriers in Capsella - Lafon-Placette, Clément; Hatorangan, Marcelinus R; Steige, Kim A; Cornille, Amandine; Lascoux, Martin; Slotte, Tanja; Köhler, Claudia (Nature plants, 2018)
Hybrid seed lethality is a widespread type of reproductive barrier among angiosperm taxa1,2 that contributes to species divergence by preventing gene flow between natural populations3,4. Besides its ecological importance, it is an important obstacle to plant breeding strategies 5 . Hybrid seed lethality is mostly due to a failure of the nourishing endosperm tissue, resulting in embryo arrest3,6,7. The cause of this failure is a parental dosage imbalance in the endosperm that can be a consequence of either differences in parental ploidy levels or differences in the 'effective ploidy', also known as the endosperm balance number (EBN)8,9. Hybrid seed defects exhibit a parent-of-origin pattern3,6,7, suggesting that differences in number or expression strength of parent-of-origin-specific imprinted genes underpin, as the primary or the secondary cause, the molecular basis of the EBN7,10. Here, we have tested this concept in the genus Capsella and show that the effective ploidy of three Capsella species correlates with the number and expression level of paternally expressed genes (PEGs). Importantly, the number of PEGs and the effective ploidy decrease with the selfing history of a species: the obligate outbreeder Capsella grandiflora had the highest effective ploidy, followed by the recent selfer Capsella rubella and the ancient selfer Capsella orientalis. PEGs were associated with the presence of transposable elements and their silencing mark, DNA methylation in CHH context (where H denotes any base except C). This suggests that transposable elements have driven the imprintome divergence between Capsella species. Together, we propose that variation in transposable element insertions, the resulting differences in PEG number and divergence in their expression level form one component of the effective ploidy variation between species of different breeding system histories, and, as a consequence, allow the establishment of endosperm-based hybridization barriers.
Keywords: DNA, Plant; Reproductive Isolation; regulace genové exprese u rostlin; Genomic Imprinting; Gene Expression Regulation, Plant; rostlinné geny; DNA Methylation; Ploidies; metylace DNA; Capsella; ploidie; genomový imprinting; Genes, Plant; Endosperm; Diploidy; DNA rostlinná; reprodukční izolace; DNA Transposable Elements; endosperm; transpozibilní elementy DNA; diploidie